Pengaruh Lama Kebuntingan Induk Terhadap Jenis Kelamin dan Bobot Lahir Pedet Sapi Bali Hasil Inseminasi Buatan - Desi Ratnasari; Jumriah Syam; Khaerani Kiramang; Muhammad Nur Hidayat; Rasyidah Mappanganro (Universitas Islam Negeri Alauddin Makassar, 2022)
This study was conducted with the aim of knowing the effect of gestation age cows on gender and calf's birth weight in bali cattle resulting by artificially insemination (AI). The material used was 52 cows and 52 calves of bali cattle. This type of research is quantitative with analytical methods based on recording the production of bali cattle and calves produced by AI in the Bantaeng Regency. Testing the data using statistical analysis of multiple linear regression, this test is to determine the effect between gestational age of the cows on gender and birth weight calves of AI bali cattle. The results of the analysis showed that the cow gestational age and calf’s gender showed a very significant effect (P<0,01) with a negative relationship value meaning that the greater the gestational age of the parent, the gender of the calf was male. While gestational age and calf’s birth weight had significant effects (P<0,05) a positive correlation indicated that the higher the gestational age of the mother, the higher the calf's birth weight. Calf birth weight had no significant effect (P>0.05) on the gender of bali cattle AI results and showed a weak relationship